Multidimensional exploration of hydrogels as biological scaffolds for spinal cord regeneration: mechanisms and future perspectives - Han, Chenxi; Jiao, Jiao; Gong, Chan; Li, Jiatao; Zhao, Min; Lu, Xiao (Frontiers in Bioengineering and Biotechnology, 2025)
Spinal cord injury (SCI) is a severe condition that frequently leads to permanent disabilities and neurological dysfunction. Its progression is driven by a multifaceted pathophysiology, encompassing direct trauma, secondary injury cascades, and intricate cellular and molecular responses. While current therapies focus on alleviating symptoms and restoring functionality, achieving effective neural regeneration in the spinal cord continues to be a significant challenge. Hydrogels, recognized for their exceptional biocompatibility, conductivity, and injectability, have shown great potential as advanced scaffolds to support neuronal and axonal regeneration. Recently, these materials have attracted significant interest in the field of SCI rehabilitation research. This review concludes recent progress in hydrogel-based strategies for SCI rehabilitation, emphasizing their distinct properties, underlying mechanisms, and integration with bioactive molecules, stem cells, and complementary biomaterials. Hydrogels foster neuronal regeneration by providing a tailored microenvironment, while advanced features such as self-repair, electrical conductivity, and controlled drug release significantly enhance their therapeutic potential in experimental models. This review explores hydrogel technologies and their applications, underscoring their potential to address the challenges of SCI treatment and paving the way for future clinical implementation.